Association between hospital volume and in‐hospital mortality following radiofrequency ablation for hepatocellular carcinoma. Issue 2 (26th July 2017) - Sato, M.; Tateishi, R.; Yasunaga, H.; Matsui, H.; Fushimi, K.; Ikeda, H.; Yatomi, Y.; Koike, K.
Abstract : Background: Radiofrequency ablation (RFA) is a minimally invasive treatment for hepatocellular carcinoma (HCC). There is increasing evidence of an association between increasing hospital volume and lower postoperative mortality for many surgical procedures, but this is difficult to establish with minimally invasive treatments, where postoperative mortality is low. The aim of this study was to investigate the relationship between hospital volume and in‐hospital mortality following RFA using a Japanese nationwide database. Methods: Data from the Diagnostic Procedure Combination database were analysed from 1 July 2010 to 31 March 2012. Multivariable logistic regression was used to analyse the relationship between hospital volume and in‐hospital mortality following RFA, with adjustment for patient background. Results: Some 36 675 patients with HCC were identified in the database. The overall in‐hospital mortality rate from RFA was 0·31 per cent. In‐hospital mortality was significantly higher in low‐volume than high‐volume hospitals (odds ratio 2·57, 95 per cent c.i. 1·61 to 4·09; P  < 0·001). Higher in‐hospital mortality was significantly associated with older age and a higher Charlson Co‐morbidity Index score. Conclusion: RFA for HCC was associated with acceptably low mortality in Japan, but in‐hospital mortality following RFA was affected by hospital procedural volume. Abstract : Hospital volume and mortality in radiofrequency ablation for hepatocellular carcinoma Hospital volume effect even with a low mortality procedure.